Front Cover Image: Volume 3 Issue 1. Issue 1 (30th March 2022) - Han, Lu; Tian, Benqiang; Gao, Xiangxiang; Zhong, Yang; Wang, Shengnan; Song, Shuchang; Wang, Zhili; Zhang, Ying; Kuang, Yun; Sun, Xiaoming
Abstract : Front cover image : High‐index facet copper catalysts are more favorable for converting CO2 to high‐value multi‐carbon products in CO2 electroreduction reduction. In this work, reconstructed Cu nanowires (Cu NWs) featured with (311) high‐index facets were obtained through square wave (SW) potential treatments. The FE of C2+ products of SW‐Cu NWs is nearly 4 times higher than that of the original Cu NWs under the same condition. The (311) high‐index facet can promote the activation of CO2 and the formation of specific *OCCOH intermediate with an accessible energy pathway of dimerization reaction. (DOI: https://doi.org/10.1002/smm2.1082 )